Effect of high-flow nasal cannula oxygen therapy compared with conventional oxygen therapy in postoperative patients: a systematic review and meta-analysis - Xiwen Zhang; Zhonghua Lu; Wei Chang; Shan-Shan Meng; Jianfeng Xie; Jing-Yuan Xu; Haibo Qiu; Fengmei Guo (BMJ Open)
Objective To evaluate the effect of high-flow nasal cannula oxygen therapy (HFNC) versus conventional oxygen therapy (COT) on the reintubation rate, rate of escalation of respiratory support and clinical outcomes in postextubation adult surgical patients.Design Systematic review and meta-analysis of published literature.Data sources PubMed, Embase, the Cochrane Library, Web of Science, China National Knowledge Index and Wan fang databases were searched up to August 2018.Eligibility criteria Studies in postoperative adult surgical patients (≥18 years), receiving HFNC or COT applied immediately after extubation that reported reintubation, escalation of respiratory support, postoperative pulmonary complications (PPCs) and mortality were eligible for inclusion.Data extraction and synthesis The following data were extracted from the included studies: first author’s name, year of publication, study population, country of origin, study design, number of patients, patients’ baseline characteristics and outcomes. Associations were evaluated using risk ratio (RR) and 95% CIs.Results This meta-analysis included 10 studies (1327 patients). HFNC significantly reduced the reintubation rate (RR 0.38, 95% CI 0.23 to 0.61, p<0.0001) and rate of escalation of respiratory support (RR 0.43, 95% CI 0.26 to 0.73, p=0.002) in postextubation surgical patients compared with COT. There were no differences in the incidence of PPCs (RR 0.87, 95% CI 0.70 to 1.08, p=0.21) or mortality (RR 0.45, 95% CI 0.16 to 1.29, p=0.14).Conclusion HFNC is associated with a significantly lower reintubation rate and rate of escalation of respiratory support compared with COT in postextubation adult surgical patients, but there is no difference in the incidence of PPCs or mortality. More well-designed, large randomised controlled trials are needed to determine the subpopulation of patients who are most likely to benefit from HFNC therapy.